0516 Characterizing Sleep and Mood during COVID for Youth with Allergic Disease. (25th May 2022) - Booster, Genery; Jump, Stephanie; Meltzer, Lisa
Abstract: Introduction: The COVID-19 pandemic significantly disrupted the daily lives of children and adolescents. This study aimed to characterize sleep and mood during COVID in youth with asthma and/or eczema at two times: shortly after the lifting of stay at home orders (Summer 2020 [T1]) and after youth returned to school (Winter 2021 [T2]). Methods: Pediatric PROMIS measures (Sleep Disturbances, Sleep-Related Impairment, Anxiety, Depressive Symptoms) and the Pediatric Sleep Practices Questionnaire were administered through REDCap. Parents of younger children (YC, 5-7 years, n=16) completed proxy measures for their children, while older children (OC, 8-12 years, n=16) and adolescents (ADOL, 13-17 years, n=17) completed self-report measures. Results: For YC, mean Sleep Disturbances T-scores significantly decreased between T1 and T2 (62.0 vs. 56.4, p=.02), with no significant changes in the other variables. For OC, there were no significant changes in mean T-scores for any of the outcomes. For ADOL, there was a significant increase in Sleep-Related Impairment between T1 and T2 (52.0 vs. 57.7, p=.003), as well as a significant increase in Depressive Symptoms (48.2 vs. 52.5, p=.04). At T1, technology use prior to bedtime was more common in ADOL (YC=37.5%, OC=37.5%, ADOL=88.2%). At T2, technology use was also more common in ADOL (YC=50.0%, OC=37.5%, ADOL=64.7%), with an increase in YC technology use and a decrease in ADOL technology use observed. Parental presence while falling asleep was greatest in YC at both time points, with no noted changes in any group across time (T1: YC=56.3%, OC=18.8%, ADOL=17.6%; T2: YC=50.0%, OC=25.0%, ADOL=11.8%). Conclusion: This study was limited by a small sample size, but provides some insights into the sleep and mood of children and adolescents with allergic disease during the first year of the COVID-19 pandemic. Although YC had fewer sleep disturbances at T2, there was an increase in technology use prior to bedtime. For ADOL, some of the changes in sleep, technology use, and depressive symptoms were likely due to the return to school at T2. Finally, it was notable that multiple OC and ADOL required parental presence to fall asleep. Additional research is needed to understand how the ongoing pandemic is impacting children and adolescents. Support (If Any):